Cultivation of Aerobic Granular Sludge Using Chitosan as A Nucleating Agent for Wastewater Treatment - KUMAR, SHARANYA; HARUN, HASNIDA (Progress in Engineering Application and Technology, 2023)
Two identical high and slender cylindrical laboratory-scale reactors with a 2 L working volume was set up in this study. Each reactor was inoculated with 1 L of activated sludge from a local food industry and operated continuously with a cycle time of 24 hours. In every cycle, 1L of synthetic wastewater was supplied with 1120 mg/L of COD concentration to each reactor. In order to investigate the effect of the addition of chitosan on the granulation process of aerobic granular sludge (AGS), 10g of chitosan was added to a reactor, while another reactor was operated as a control reactor.After 16 days of operation, the reactor with the addition of chitosan showed higher removal efficiency of COD which is 40% compared to the control reactor, which is 42%. Meanwhile, MLSS and MLVSS in the reactor with chitosan increased up to 4780 mg/L of MLSS and 3560 mg/L MLVSS, higher than the control reactor with 3850 mg/L of MLSS and 2560 mg/L of MLVSS. Furthermore, AGS round in shape, compact and brown in color with an average size of 5.62mm was successfully cultivated in reactors with the addition of chitosan after 16 days of operation. Meanwhile, AGS in the control reactor was developed into an average size of 4.13mm.In a conclusion, the AGS system with supplemented chitosan is proven to accelerate granule cultivation without compromising the effluent quality. Therefore, AGS can be an advantageous treatment system to be implemented in the wastewater industry as it has good performance in degrading organic and nutrient in wastewater besides it is environmentally friendly, low cost, and can improve the performance of the conventional wastewater treatment sector.